Duality invariance and cosmological dynamics - Chimento, Luis Pascual (2008)
A duality transformation that interrelates expanding and contracting cosmological models is shown to single out a duality invariant, interacting two-component description of any irrotational, geodesic and shear-free cosmic medium with vanishing three-curvature scalar. We have applied this feature to a system of matter and radiation, to a mixture of dark matter and dark energy, to minimal and conformal scalar fields, and to an enlarged Chaplygin gas model of the cosmic substratum. We have extended the concept of duality transformations to cosmological perturbations and demonstrated the invariance of adiabatic pressure perturbations under these transformations. © 2008 World Scientific Publishing company.